Handling Children Who Commit Crimes Under the Criminal Justice System - Hadi Tuasikal; Asmuruf, Johana (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
The purpose of this study is to find out how the handling of criminal acts committed by minors based on the juvenile justice system. Using normative legal research methods, it is concluded: 1. In the Criminal Code, there are two kinds of elements, namely objective elements and subjective elements. The objective element is the element related to the situation, which is the state in which the actions of the perpetrator must be carried out, while the subjective element is the element inherent in the perpetrator or related to the perpetrator. The subjective element of a criminal act is intentional or accidental (dolus or culpa); purpose or intention on an experiment or poging as referred to in Article 53 paragraph 1 of the Criminal Code. The objective element of a criminal act is the unlawful nature or wederrechtelijkheid; the quality of the perpetrator, for example